Human rhinovirus infection and COPD: role in exacerbations and potential for therapeutic targets. (2nd August 2020) - Cafferkey, John; Coultas, James Andrew; Mallia, Patrick
ABSTRACT: Introduction: Respiratory virus infections (predominantly rhinoviruses) are the commonly identified in COPD exacerbations but debate about their role as a trigger of exacerbations continues. Experimental infection studies have provided significant new evidence establishing a causal relationship between virus infection and COPD exacerbations and contributed to a better understanding of the mechanisms of virus-induced exacerbations. However as yet no anti-viral treatments have undergone clinical trials in COPD patients. Areas covered: This review discusses the evidence for and against respiratory viruses being the main trigger of COPD exacerbations from both epidemiological studies and experimental infection studies. The host immune response to rhinovirus infection and how abnormalities in host immunity may underlie increased susceptibility to virus infection in COPD are discussed and the role of dual viral-bacterial infection in COPD exacerbations. Finally the current state of anti-viral therapy is discussed and how these may be used in the future treatment of COPD exacerbations. Expert opinion: Respiratory virus infections are the trigger of a substantial proportion of COPD exacerbations and rhinoviruses are the most common virus type. Clinical trials of anti-viral agents are needed in COPD patients to determine whether they are effective in virus-induced COPD exacerbations.